Thickening agent for fracturing fluid and preparation method thereof

By adding modified konjac glue and other natural materials to the thickener for fracturing liquid, cross-linking reaction and hydrogen bond formation improve the viscosity and cross-linking performance of the thickener, the problem of decreasing the viscosity of the fracturing liquid under high temperature conditions is solved, and more efficient fracturing operations and lower environmental pollution are achieved.

CN119614177AActive Publication Date: 2025-03-14SHAANXI WANDE PETROLEUM TECH CO LTD

Patent Information

Application Number
CN202510153743.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

Under high temperature conditions, the viscosity performance of the fracturing fluid decreases, affecting the effect of fracturing operations.

Method used

A thickening agent for fracturing liquid is used, which includes liquid material and solid material. The liquid material is composed of deionized water and N-methylpyrrolidone. Modified konjac gum, chitosan, diatomaceous earth, ceramide and other components are added to the solid material, and the viscosity and crosslinking performance of the thickening agent are improved through crosslinking reactions and hydrogen bond formation.

Benefits of technology

It effectively improves the viscosity and cross-linking performance of the thickener, improves the sand carrying capacity and fracturing effect of the fracturing fluid, and reduces the filtration loss and reduces the pollution to the soil in the formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of thickening agents, in particular to a thickening agent for fracturing fluid and a preparation method of the thickening agent, the thickening agent comprises a liquid material and a solid material, the mass ratio of the liquid material to the solid material is 1: (2.2-2.4), and the liquid material is composed of deionized water and N-methyl pyrrolidone. According to the preparation method disclosed by the invention, the konjaku flour is added in the preparation of the thickening agent, and after the konjaku flour is subjected to mixing reaction and curing treatment, amino functional groups in konjaku molecules can be subjected to cross-linking reaction with aldehyde groups of glutaraldehyde, so that water molecules are wrapped in a cross-linked network structure, and the internal friction force during fluid flowing is increased; and hydroxyl groups on molecular chains of the konjac glucomannan and aldehyde groups of glutaraldehyde are subjected to a condensation reaction to form covalent bonds, so that a cross-linking effect is achieved, a stable chemical cross-linked network structure is formed among the molecular chains of the konjac glucomannan, and the cross-linking performance of the thickening agent is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thickeners, in particular to a thickener for fracturing fluid and a preparation method thereof. Background Art

[0002] Fracturing fluid thickener is a chemical additive used to increase the viscosity of fracturing fluid and plays a key role in fracturing operations in oil and gas extraction.

[0003] In the prior art, during fracturing operations, as the depth of the formation increases and the temperature rises, the forces between molecular chains will be weakened under high temperature conditions, resulting in a decrease in the degree of entanglement of the molecular chains, which affects the viscosity of the fracturing fluid. Based on this, the present invention provides a thickener for fracturing fluid and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a thickener for fracturing fluid and a preparation method thereof. The thickener for fracturing fluid prepared by the present invention not only has good viscosity, but also has excellent cross-linking performance, which effectively improves the performance of the thickener.

[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a thickener for a fracturing fluid, comprising a liquid material and a solid material, wherein the mass ratio of the liquid material to the solid material is 1:(2.2-2.4); The liquid material consists of deionized water and N-methylpyrrolidone, and the mass ratio of the deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 20 to 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 10 to 20 parts of acrylic acid, 10 to 20 parts of acrylamide, 8 to 10 parts of hydroxypropyl methacrylate, 4 to 6 parts of konjac gum, 2 to 4 parts of chitosan, 1 to 3 parts of diatomaceous earth, 0.4 to 0.6 parts of ceramsite, 0.4 to 0.6 parts of disodium ethylenediaminetetraacetate, 0.2 to 0.4 parts of chain transfer agent and 0.2 to 0.4 parts of initiator; Described konjac glucomannan is subjected to modification treatment, and the modification treatment of described konjac glucomannan comprises the following steps: S1: Konjac gum is mixed and reacted to obtain a mixed solution; S2: The mixed solution is solidified to complete the modification of the konjac gum.

[0006] Furthermore, the chain transfer agent is at least one of sodium formate, sodium sulfate and sodium citrate.

[0007] Furthermore, the initiator is sodium bisulfite.

[0008] Furthermore, the konjac gum is powdered and has a particle size of 140 to 200 meshes.

[0009] Furthermore, the mixed solution is prepared by the following method: the konjac gum and the carbendazide solution are added to a mixer, the mixer is set at 220-240 r / min and stirred for 8-12 minutes, after being mixed evenly, the mixture is added to a water bath, heated to 50-60° C., stirring is maintained during the heating process, and then the mixture is kept warm for reaction for 16-20 minutes. After cooling to room temperature, a sodium carbonate solution is added, stirred evenly, and allowed to stand for 6-10 minutes to obtain a mixed solution.

[0010] Furthermore, the mass of the carbendaldehyde solution is 2 to 3 times the mass of konjac gum, the concentration of the carbendaldehyde solution is 2 to 4%, the mass of the sodium carbonate solution is 10 to 20% of the mass of konjac gum, and the concentration of the sodium carbonate solution is 4 to 6%.

[0011] Furthermore, the solidification treatment method is: filtering and separating the mixed liquid to obtain a solid product, washing the solid product, and then sending it into an oven, setting the oven at 60-70° C. and drying it at 40-50° C., grinding and sieving after drying, the sieved particle size is 140-200 meshes, and the modification treatment of konjac gum is completed.

[0012] Further, the acrylic acid and hydroxypropyl methacrylate are pretreated to obtain an additive liquid, and the additive liquid is obtained by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of the deionized water is 70-80% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.1-0.3), after mixing, ammonium persulfate solution is added, the temperature is raised to 60-80°C, the reactor is kept in a stirring state, the speed is 120-160r / min, after heating, p-toluenesulfonic acid solution is added, the temperature is kept for reaction for 2-3h, ammonia water is added to adjust the pH value to 8-9, and the additive liquid is obtained, wherein the mass of the ammonium persulfate solution is 6-10% of the mass of the acrylic acid, and the concentration is 2-4%, and the mass of the p-toluenesulfonic acid solution is 4-6% of the mass of the acrylic acid, and the concentration is 1-3%.

[0013] Furthermore, the chitosan, diatomaceous earth and ceramsite are all powdered materials with a particle size of 200 to 300 meshes.

[0014] In a second aspect, the present invention further provides a method for preparing a thickener for fracturing fluid, comprising the following steps: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reaction kettle, set the mixing process at 80-120 r / min for 6-10 min, add the additive liquid after mixing, set the mixing process at 120-160 r / min for 12-16 min, and obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it stand and react for 20 to 30 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set 80 to 120 r / min to mix for 20 to 30 minutes, continuously introduce nitrogen during the mixing process, add the initiator after mixing, mix well and react for 3 to 6 hours to obtain a thickener for fracturing fluid.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1, among the present invention, by adding of konjac flour in thickening agent preparation, konjac flour after hybrid reaction, solidification treatment, the amino functional group in the konjac molecule can cross-link reaction with the aldehyde group of glutaraldehyde, so that water molecules are wrapped in the cross-linked network structure, the internal friction force when increasing the fluid flow, namely played the effect of promoting the viscosity of the thickening agent, the hydroxyl on the konjac glucomannan molecular chain and the aldehyde group of glutaraldehyde condensation reaction form covalent bond, play a cross-linked effect, make between the konjac glucomannan molecular chain, form stable chemical cross-linked network structure, effectively improve the cross-linking property of thickening agent.

[0016] 2. In the present invention, by adding chitosan, diatomaceous earth and ceramsite, the hydrophilic groups contained in the chitosan molecular chain can form hydrogen bonds with water molecules, are evenly distributed in the fracturing fluid and play a entanglement role, effectively improving the viscosity of the fracturing fluid and enhancing its sand carrying capacity. By utilizing the rich pore structure of diatomaceous earth and ceramsite, which have a large specific surface area, tiny filtration channels can be formed in the fracturing fluid, preventing solid particles and impurities in the fracturing fluid from entering the formation, reducing the filtration loss, and improving the fracturing effect. By adding the above-mentioned natural materials, the natural materials can be naturally degraded in the natural environment, reducing the pollution to the formation soil.

[0017] 3. In the present invention, acrylic acid and hydroxypropyl methacrylate are pretreated to cause a cross-linking reaction between acrylic acid and hydroxypropyl methacrylate, forming a branched structure in the acrylic acid molecular chain, which reduces the number of freely moving molecular chains and increases the fluid resistance, thereby achieving the purpose of increasing the viscosity of the fracturing fluid. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] This embodiment provides a thickener for fracturing fluid, including a liquid material and a solid material, wherein the mass ratio of the liquid material to the solid material is 1:(2.2-2.4); The liquid material is composed of deionized water and N-methylpyrrolidone, and the mass ratio of deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 20 to 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 10 to 20 parts of acrylic acid, 10 to 20 parts of acrylamide, 8 to 10 parts of hydroxypropyl methacrylate, 4 to 6 parts of konjac gum, 2 to 4 parts of chitosan, 1 to 3 parts of diatomaceous earth, 0.4 to 0.6 parts of ceramsite, 0.4 to 0.6 parts of disodium ethylenediaminetetraacetate, 0.2 to 0.4 parts of chain transfer agent and 0.2 to 0.4 parts of initiator; Konjac glucomannan is subjected to modification treatment, and the modification treatment of konjac glucomannan comprises the following steps: S1: Konjac gum is mixed and reacted to obtain a mixed solution; S2: The mixed solution is solidified to complete the modification of the konjac gum.

[0020] In some embodiments, the chain transfer agent is at least one of sodium formate, sodium sulfate, and sodium citrate.

[0021] In some embodiments, the initiator is sodium bisulfite.

[0022] In some embodiments, konjac gum is selected as powder with a particle size of 140-200 meshes.

[0023] In some embodiments, the mixed solution is prepared by the following method: konjac gum and carbodialdehyde solution are added to a mixer, the mixer is set to 220-240r / min and stirred for 8-12 minutes, after mixing evenly, added to a water bath, heated to 50-60°C, stirring is maintained during the heating process, and then the mixture is kept warm for 16-20 minutes. After cooling to room temperature, sodium carbonate solution is added, stirred evenly, and allowed to stand for 6-10 minutes to obtain a mixed solution.

[0024] In some embodiments, the mass of the tantalum dialdehyde solution is 2 to 3 times the mass of konjac gum, the concentration of the tantalum dialdehyde solution is 2 to 4%, the mass of the sodium carbonate solution is 10 to 20% of the mass of the konjac gum, and the concentration of the sodium carbonate solution is 4 to 6%.

[0025] In some embodiments, the solidification treatment method is: the mixed liquid is filtered and separated to obtain a solid product, the solid product is washed, and then sent to an oven, the oven is set at 60-70°C and dried at 40-50°C, and after drying, it is ground and sieved, and the sieved particle size is 140-200 mesh, thereby completing the modification of konjac gum.

[0026] In some embodiments, acrylic acid and hydroxypropyl methacrylate are pretreated to prepare an additive liquid, and the additive liquid is prepared by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of deionized water is 70-80% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.1-0.3), and after mixing, ammonium persulfate solution is added, and the temperature is raised to 60-80°C. The reactor is kept in a stirring state with a speed of 120-160r / min. After heating, p-toluenesulfonic acid solution is added, and the reaction is kept warm for 2-3h, and ammonia water is added to adjust the pH value to 8-9 to prepare an additive liquid, wherein the mass of the ammonium persulfate solution is 6-10% of the mass of the acrylic acid, and the concentration is 2-4%, and the mass of the p-toluenesulfonic acid solution is 4-6% of the mass of the acrylic acid, and the concentration is 1-3%.

[0027] In some embodiments, chitosan, diatomaceous earth and ceramsite are all powdered materials with a particle size of 200-300 meshes.

[0028] In some embodiments, a method for preparing a thickener for a fracturing fluid comprises the following steps: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reaction kettle, set the mixing process at 80-120 r / min for 6-10 min, add the additive liquid after mixing, set the mixing process at 120-160 r / min for 12-16 min, and obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it stand and react for 20 to 30 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set 80 to 120 r / min to mix for 20 to 30 minutes, continuously introduce nitrogen during the mixing process, add the initiator after mixing, mix well and react for 3 to 6 hours to obtain a thickener for fracturing fluid.

[0029] In the present embodiment, by adding of konjac flour in thickening agent preparation, konjac flour after mixing reaction, curing treatment, the amino functional group in the konjac molecule can cross-link with the aldehyde group of glutaraldehyde, so that water molecules are wrapped in the cross-linked network structure, the internal friction force during fluid flow is increased, namely, the effect of promoting the viscosity of the thickening agent is played, the hydroxyl group on the konjac glucomannan molecular chain and the aldehyde group of glutaraldehyde undergo condensation reaction to form a covalent bond, which plays a cross-linked effect, so that stable chemical cross-linked network structure is formed between the konjac glucomannan molecular chains, the cross-linking property of the thickening agent is effectively improved, by adding of chitosan, diatomaceous earth and ceramsite, the hydrophilic group contained in the chitosan molecular chain is utilized, hydrogen bonds can be formed with water molecules, and the thickening agent can be uniformly dispersed in the fracturing fluid. The even distribution and entanglement effect effectively increase the viscosity of the fracturing fluid and enhance its sand carrying capacity. The rich pore structure of diatomaceous earth and ceramsite has a large specific surface area, which can form tiny filtration channels in the fracturing fluid to prevent solid particles and impurities in the fracturing fluid from entering the formation, reduce filtration loss, and improve the fracturing effect. Through the addition of the above-mentioned natural materials, the natural materials can be naturally degraded in the natural environment to reduce the pollution of the formation soil. Through the pretreatment of acrylic acid and hydroxypropyl methacrylate, acrylic acid and hydroxypropyl methacrylate undergo a cross-linking reaction to form a branched structure in the acrylic acid molecular chain, which reduces the free-moving molecular chains and increases the fluid resistance, thereby achieving the purpose of increasing the viscosity of the fracturing fluid.

[0030] Based on the above embodiments, the following experiments were performed: It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0031] Experiment 1: Raw material preparation: The mass ratio of liquid material to solid material is 1:(2.2); The liquid material is composed of deionized water and N-methylpyrrolidone, and the mass ratio of deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 20 parts of 2-acrylamide-2-methylpropane sulfonic acid, 10 parts of acrylic acid, 10 parts of acrylamide, 8 parts of hydroxypropyl methacrylate, 4 parts of konjac gum, 2 parts of chitosan, 1 part of diatomaceous earth, 0.4 parts of ceramsite, 0.4 parts of disodium ethylenediaminetetraacetate, 0.2 parts of chain transfer agent and 0.2 parts of initiator, the chain transfer agent is sodium formate, the initiator is sodium bisulfite, the konjac gum is powdered material with a particle size of 140 meshes, and the chitosan, diatomaceous earth and ceramsite are all powdered material with a particle size of 200 meshes; Konjac glucomannan is subjected to modification treatment, and the modification treatment of konjac glucomannan comprises the following steps: S1: Konjac gum is mixed and reacted to obtain a mixed solution; The mixed solution is prepared by the following method: konjac gum and ferric anhydride solution are added to a mixer, the mixer is set to 220r / min and stirred for 8 minutes, after being mixed evenly, the mixture is added to a water bath, heated to 50°C, stirred during the heating process, and then kept warm for 16 minutes, after cooling to room temperature, sodium carbonate solution is added, stirred evenly, and allowed to stand for 6 minutes to prepare a mixed solution, wherein the mass of ferric anhydride solution is twice that of konjac gum, the concentration of ferric anhydride solution is 2%, the mass of sodium carbonate solution is 10% of the mass of konjac gum, and the concentration of sodium carbonate solution is 4%; S2: the mixed solution is solidified to complete the modification of konjac gum; The solidification treatment method is as follows: the mixed liquid is filtered and separated to obtain a solid product, the solid product is washed, and then sent to an oven, the oven is set at 60° C. and dried at 40° C., and after the drying, the mixture is ground and sieved, and the sieved particle size is 140 meshes, thereby completing the modification of the konjac gum; Acrylic acid and hydroxypropyl methacrylate are pretreated to prepare an additive liquid, and the additive liquid is prepared by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of deionized water is 70% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.1), after mixing, ammonium persulfate solution is added, the temperature is raised to 60°C, the reactor is kept in a stirring state, the speed is 120r / min, after heating, p-toluenesulfonic acid solution is added, the temperature is kept for reaction for 2h, ammonia water is added to adjust the pH value to 8, and the additive liquid is prepared, wherein the mass of the ammonium persulfate solution is 6% of the mass of acrylic acid and the concentration is 2%, and the mass of the p-toluenesulfonic acid solution is 4% of the mass of acrylic acid and the concentration is 1%; Preparation of fracturing fluid thickener: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reactor, set the mixing process at 80 r / min for 6 min, add the additive liquid after mixing, set the mixing process at 120 r / min for 12 min, and obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it stand and react for 20 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set 80r / min to mix for 20 minutes, continuously introduce nitrogen during the mixing process, add initiator after mixing is completed, mix well and react for 3 hours to obtain a thickener for fracturing fluid.

[0032] Experiment 2: Raw material preparation: The mass ratio of liquid material to solid material is 1:(2.3); The liquid material is composed of deionized water and N-methylpyrrolidone, and the mass ratio of deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 25 parts of 2-acrylamide-2-methylpropane sulfonic acid, 15 parts of acrylic acid, 15 parts of acrylamide, 9 parts of hydroxypropyl methacrylate, 5 parts of konjac glucomannan, 3 parts of chitosan, 2 parts of diatomaceous earth, 0.5 parts of ceramsite, 0.5 parts of disodium ethylenediaminetetraacetate, 0.3 parts of chain transfer agent and 0.3 parts of initiator, wherein the chain transfer agent is sodium sulfate, the initiator is sodium bisulfite, the konjac glucomannan is powdered material with a particle size of 170 meshes, and the chitosan, diatomaceous earth and ceramsite are all powdered material with a particle size of 250 meshes; Konjac glucomannan is subjected to modification treatment, and the modification treatment of konjac glucomannan comprises the following steps: S1: Konjac gum is mixed and reacted to obtain a mixed solution; The mixed solution is prepared by the following method: konjac gum and ferric anhydride solution are added to a mixer, the mixer is set to 230r / min and stirred for 10 minutes, after being mixed evenly, the mixture is added to a water bath, heated to 55°C, stirred during the heating process, and then kept warm for 18 minutes, after cooling to room temperature, sodium carbonate solution is added, stirred evenly, and allowed to stand for 8 minutes to obtain a mixed solution, wherein the mass of ferric anhydride solution is 2.5 times the mass of konjac gum, the concentration of ferric anhydride solution is 3%, the mass of sodium carbonate solution is 15% of the mass of konjac gum, and the concentration of sodium carbonate solution is 5%; S2: the mixed solution is solidified to complete the modification of konjac gum; The solidification treatment method is as follows: the mixed liquid is filtered and separated to obtain a solid product, the solid product is washed, and then sent to an oven, the oven is set at 65° C. and dried at 45° C., and after the drying, the powder is ground and sieved, and the sieved particle size is 170 meshes, thereby completing the modification of the konjac gum; Acrylic acid and hydroxypropyl methacrylate are pretreated to prepare an additive liquid, and the additive liquid is prepared by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of deionized water is 75% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.2), and after mixing, ammonium persulfate solution is added, and the temperature is raised to 70°C. The reactor is kept in a stirring state with a speed of 140r / min. After heating, p-toluenesulfonic acid solution is added, and the temperature is kept for reaction for 2.5h, and ammonia water is added to adjust the pH value to 8.5 to prepare an additive liquid, wherein the mass of the ammonium persulfate solution is 8% of the mass of acrylic acid and the concentration is 3%, and the mass of the p-toluenesulfonic acid solution is 5% of the mass of acrylic acid and the concentration is 2%; Preparation of fracturing fluid thickener: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reactor, set the mixing speed at 100 r / min for 8 minutes, add the additive liquid after mixing, set the mixing speed at 140 r / min for 14 minutes to obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it react for 25 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set the mixing speed to 100r / min for 25 minutes, continuously introduce nitrogen during the mixing process, add the initiator after the mixing is completed, mix well and react for 4.5 hours to obtain a thickener for fracturing fluid.

[0033] Experiment 3: Raw material preparation: The mass ratio of liquid material to solid material is 1:(2.4); The liquid material is composed of deionized water and N-methylpyrrolidone, and the mass ratio of deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 20 parts of acrylic acid, 20 parts of acrylamide, 10 parts of hydroxypropyl methacrylate, 6 parts of konjac glucomannan, 4 parts of chitosan, 3 parts of diatomaceous earth, 0.6 parts of ceramsite, 0.6 parts of disodium ethylenediaminetetraacetate, 0.4 parts of chain transfer agent and 0.4 parts of initiator, wherein the chain transfer agent is sodium citrate, the initiator is sodium bisulfite, the konjac glucomannan is powdered material with a particle size of 200 meshes, and the chitosan, diatomaceous earth and ceramsite are all powdered material with a particle size of 300 meshes; Konjac glucomannan is subjected to modification treatment, and the modification treatment of konjac glucomannan comprises the following steps: S1: Konjac gum is mixed and reacted to obtain a mixed solution; The mixed solution is prepared by the following method: konjac gum and ferric anhydride solution are added to a mixer, the mixer is set to 240r / min and stirred for 12 minutes, after being mixed evenly, the mixture is added to a water bath, heated to 60°C, stirred during the heating process, and then kept warm for 20 minutes, after cooling to room temperature, sodium carbonate solution is added, stirred evenly, and allowed to stand for 10 minutes to prepare a mixed solution, wherein the mass of ferric anhydride solution is 3 times the mass of konjac gum, the concentration of ferric anhydride solution is 4%, the mass of sodium carbonate solution is 20% of the mass of konjac gum, and the concentration of sodium carbonate solution is 6%; S2: the mixed solution is solidified to complete the modification of konjac gum; The solidification treatment method is as follows: the mixed liquid is filtered and separated to obtain a solid product, the solid product is washed, and then sent to an oven, the oven is set at 70° C. and dried at 50° C., and after the drying, the mixture is ground and sieved, and the sieved particle size is 200 meshes, thereby completing the modification of the konjac gum; Acrylic acid and hydroxypropyl methacrylate are pretreated to prepare an additive liquid, and the additive liquid is prepared by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of deionized water is 80% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.3), after mixing, ammonium persulfate solution is added, the temperature is raised to 80°C, the reactor is kept in a stirring state, the speed is 160r / min, after heating, p-toluenesulfonic acid solution is added, the temperature is kept for reaction for 3h, ammonia water is added to adjust the pH value to 9, and the additive liquid is prepared, wherein the mass of the ammonium persulfate solution is 10% of the mass of acrylic acid and the concentration is 4%, and the mass of the p-toluenesulfonic acid solution is 6% of the mass of acrylic acid and the concentration is 3%; Preparation of fracturing fluid thickener: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reactor, set the mixing process at 120 r / min for 10 min, add the additive liquid after mixing, set the mixing process at 160 r / min for 16 min, and obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it react for 30 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set the 120r / min mixing process for 30 minutes, continuously introduce nitrogen during the mixing process, add the initiator after the mixing is completed, mix well and react for 6 hours to obtain a thickener for fracturing fluid.

[0034] Comparative Example 1: The difference between this comparative example and Experiment 1 is that acrylic acid and hydroxypropyl methacrylate are not pretreated in this comparative example.

[0035] Comparative Example 2: The difference between this comparative example and Experiment 1 is that this comparative example does not contain chitosan, diatomaceous earth and ceramsite.

[0036] Comparative Example 3: The difference between this comparative example and Experiment 1 is that this comparative example does not contain konjac gum.

[0037] Comparative Example 4: The difference between this comparative example and Experiment 1 is that the konjac gum is not modified in this comparative example.

[0038] Performance test: The thickeners prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were subjected to performance tests, and the test data obtained are recorded in the following table: Table 1, 0.1% thickener concentration performance test table:

[0039] Table 2, 0.5% thickener concentration performance test table:

[0040] By comparing and analyzing the relevant data in the table, it can be seen that the thickener for fracturing fluid prepared by the present invention not only has good viscosity, but also has excellent cross-linking performance. This shows that the thickener for fracturing fluid and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0041] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0042] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A thickener for fracturing fluid, characterized in that: It includes liquid material and solid material, wherein the mass ratio of the liquid material to the solid material is 1:(2.2-2.4); The liquid material consists of deionized water and N-methylpyrrolidone, and the mass ratio of the deionized water to N-methylpyrrolidone is 8.5:1.5; The solid material comprises the following raw materials in parts by weight: 20 to 30 parts of 2-acrylamide-2-methylpropane sulfonic acid, 10 to 20 parts of acrylic acid, 10 to 20 parts of acrylamide, 8 to 10 parts of hydroxypropyl methacrylate, 4 to 6 parts of konjac gum, 2 to 4 parts of chitosan, 1 to 3 parts of diatomaceous earth, 0.4 to 0.6 parts of ceramsite, 0.4 to 0.6 parts of disodium ethylenediaminetetraacetate, 0.2 to 0.4 parts of chain transfer agent and 0.2 to 0.4 parts of initiator; Described konjac glucomannan is subjected to modification treatment, and the modification treatment of described konjac glucomannan comprises the following steps: S1: Konjac gum mixed reaction to obtain a mixed solution; S2: The mixed solution is solidified to complete the modification of the konjac gum.

2. The thickener for fracturing fluid according to claim 1, characterized in that: The chain transfer agent is at least one of sodium formate, sodium sulfate and sodium citrate.

3. The thickener for fracturing fluid according to claim 1, characterized in that: The initiator is sodium bisulfite.

4. The thickener for fracturing fluid according to claim 1, characterized in that: The konjac gum is powdered material with a particle size of 140 to 200 meshes.

5. The thickener for fracturing fluid according to claim 1, characterized in that: The mixed solution is prepared by the following method: the konjac gum and the carbendazide solution are added into a mixer, the mixer is set at 220-240 r / min and stirred for 8-12 minutes, after being mixed evenly, the mixture is added into a water bath, heated to 50-60° C., stirring is maintained during the heating process, and then the mixture is kept warm for reaction for 16-20 minutes, after being cooled to room temperature, a sodium carbonate solution is added, stirred evenly, and allowed to stand for 6-10 minutes to prepare a mixed solution.

6. The thickener for fracturing fluid according to claim 5, characterized in that: The mass of the ferric anhydride solution is 2 to 3 times that of konjac gum, and the concentration of the ferric anhydride solution is 2 to 4%. The mass of the sodium carbonate solution is 10 to 20% of that of the konjac gum, and the concentration of the sodium carbonate solution is 4 to 6%.

7. The thickener for fracturing fluid according to claim 1, characterized in that: The solidification treatment method comprises the following steps: filtering and separating the mixed liquid to obtain a solid product, washing the solid product, and then sending the solid product into an oven, wherein the oven is set at 60-70° C. and dried at 40-50° C. After the drying, the mixed liquid is ground and sieved, and the sieved particle size is 140-200 meshes, thereby completing the modification of the konjac gum.

8. The thickener for fracturing fluid according to claim 1, characterized in that: The acrylic acid and hydroxypropyl methacrylate are pretreated to prepare an additive liquid, and the additive liquid is prepared by the following method: acrylic acid and hydroxypropyl methacrylate are mixed in a reactor, deionized water and sodium dodecylbenzene sulfonate are added to the reactor, the mass of the deionized water is 70-80% of the mass of acrylic acid, and the mass ratio of deionized water to sodium dodecylbenzene sulfonate is 1:(0.1-0.3), after mixing, ammonium persulfate solution is added, the temperature is raised to 60-80°C, the reactor is kept in a stirring state, the speed is 120-160r / min, after heating, p-toluenesulfonic acid solution is added, the temperature is kept for reaction for 2-3h, ammonia water is added to adjust the pH value to 8-9, and the additive liquid is prepared, wherein the mass of the ammonium persulfate solution is 6-10% of the mass of the acrylic acid, and the concentration is 2-4%, and the mass of the p-toluenesulfonic acid solution is 4-6% of the mass of the acrylic acid, and the concentration is 1-3%.

9. The thickener for fracturing fluid according to claim 1, characterized in that: The chitosan, diatomaceous earth and ceramsite are all powdered materials with a particle size of 200-300 meshes.

10. A method for preparing a thickener for fracturing fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh deionized water, N-methylpyrrolidone and 2-acrylamide-2-methylpropanesulfonic acid as needed and add them into the reaction kettle, set the mixing process at 80-120 r / min for 6-10 min, add the additive liquid after mixing, set the mixing process at 120-160 r / min for 12-16 min, and obtain a preliminary reaction solution; Step 2: Weigh the modified konjac gum in the preliminary reaction solution as needed, let it stand and react for 20 to 30 minutes, then weigh acrylamide, chitosan, diatomaceous earth, ceramsite, disodium ethylenediaminetetraacetic acid and chain transfer agent as needed, set 80 to 120 r / min to mix for 20 to 30 minutes, continuously introduce nitrogen during the mixing process, add the initiator after mixing, mix well and react for 3 to 6 hours to obtain a thickener for fracturing fluid.

Citation Information

Patent Citations

  • Densifier for aqueous fracturing fluid and preparation method thereof

    CN103484096A

  • High temperature-resistant acidic cross-linked polymer thickening agent, and preparation method and application thereof

    CN104109219A

  • Dual mechanism thickening agents for hydraulic fracturing fluids

    CN105189643A

  • Pre-mixed sand thickener for water-base fracturing and preparation method of premix sand thickener

    CN105199707A

  • Polymer fracturing fluid system resistant to superhigh temperature

    CN110423602A

Cited By

  • Composite fracturing fluid densifier for oil and gas well and preparation process of composite fracturing fluid densifier

    CN120865877A

  • Composite fracturing fluid thickening agent for oil and gas well and preparation process thereof

    CN120865877B